Novel algorithms for the pragmatic use of ultrasound in the management of patients with rheumatoid arthritis: from diagnosis to remission - Maria Antonietta D’Agostino; Lene Terslev; Richard J. Wakefield; Mikkel Østergaard; Péter Bálint; Esperanza Naredo; Annamaria Iagnocco; Marina Backhaus; Walter Grassi; Paul Emery (2016)
The absence of specific guidance on how to use ultrasound (US) to diagnose and manage patients with inflammatory arthritis, especially with rheumatoid arthritis (RA) has hindered the optimal utilisation of US in clinical practice, potentially limiting its benefits for patient outcomes. In view of this, a group of musculoskeletal US experts formed a working group to consider how this unmet need could be satisfied and to produce guidance (additional to European League against Rheumatism (EULAR) imaging recommendations) to support clinicians in their daily clinical work. This paper describes this process and its outcome, namely five novel algorithms, which identify when US could be used. They are designed to aid diagnosis, to inform assessment of treatment response/disease monitoring and to evaluate stable disease state or remission in patients with suspected or established RA, by providing a pragmatic template for using US at certain time points of the RA management. A research agenda has also been defined for answering unmet clinical needs.